THE INFLUENCE OF THE HUMAN DEVELOPMENT INDEX, POPULATION, AND PROVINCIAL MINIMUM WAGE ON THE UNEMPLOYMENT RATE BY AN ISLAMIC ECONOMIC PERSPECTIVE IN LAMPUNG PROVINCE, 2019-2023 - Utomo, Salsabrina Nanda Saski; Hanif; Fitri, Ainul (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to analyze the influence of the Human Development Index, inhabitants Size, andProvincial Minimum Wage on the Unemployment Rate in Lampung Province over a five-year period,by 2019 to 2023. This study was employed by an Islamic economic perspective. The method used isa quantitative approach, collecting secondary data by the Central Statistics Agency covering 15districts and cities in Lampung Province. The analysis was employed utilizing panel data regressionby the hand of Eviews 12 software. The outcomes drew that the human enhancement index andinhabitants have a favorable and substantial influence on the unemployment rate, whilst theprovincial minimum wage has a favorable but insubstantial influence. This study gives importantexplanations regarding the human enhancement index, inhabitants, and provincial minimum wageon the unemployment rate by an Islamic economic perspective, that encourages its followers to workand produce, even making it an obligation for those who are able. This study emphasizes the needfor effective policies to enhance the public assistance of the society in order to overcome the problemof unemployment in Lampung.